Morphology of the tympanic‐basicranial region in Mirounga leonina (Phocidae, Carnivora), postnatal ontogeny and sexual dimorphism. Issue 4 (31st March 2015) - Loza, C. M.; Scarano, A. C.; Soibelzon, L. H.; Negrete, J.; Carlini, A. A.
Abstract The auditory region of pinnipeds has seldom been described. Here we describe and analyze the ontogenetic trajectory of the tympanic bulla of the southern elephant seal, Mirounga leonina (Phocidae, Mammalia). This species is extremely sexually dimorphic and highly polygynous (organized in harems). We examined 118 specimens, arranged in three age classes (CI, CII, and CIII), ranging from newborn to adults (males and females). To analyze the overall size and shape of the tympanic bulla we performed a geometric morphometric analysis including 87 skulls. Females reach definitive shape and size of the bulla at earlier ontogenetic stages than males, in agreement with their earlier involvement in reproductive activities. The internal anatomy of the tympanic region (e.g. form and extension of the paries) does not show remarkable differences between sexes or age classes. The greatest differences between age classes are related to bone thickness, resulting from the apposition of new annual layers. An examination of possible sex‐related external differences among age classes shows significant shape differences between males and females in CIII. The morphology observed in neonates is conserved across all individuals from CI, which included specimens up to 1 year old. Clear morphological differences were observed between CI individuals, on one hand, and CII individuals plus CIII females on the other. During cranial development of both male and females, the glenoid cavity expands and compresses the bulla; this condition reaches its maximum expression in CIII males. CIII males showed the greatest morphological differences, with respect to both CI and CII individuals, and CIII females.